Polysaccharide, the Active Component of Dendrobium officinale, Ameliorates Metabolic Hypertension in Rats via Regulating Intestinal Flora-SCFAs-Vascular Axis - Li, Bo; Wang, Hui-Ying; Huang, Jia-Hui; Xu, Wan-Feng; Feng, Xiao-Jie; Xiong, Ze-Ping; Dong, Ying-Jie; Li, Lin-Zi; He, Xinglishang; Wu, Han-Song; Zhang, Ke; Su, Jie; et al. (Frontiers in Pharmacology, 2022)
Metabolic hypertension (MH) is the most common type of hypertension worldwide because of unhealthy lifestyles, such as excessive alcohol intake and high-sugar/high-fat diets (ACHSFDs), adopted by humans. Poor diets lead to a decrease in the synthesis of short-chain fatty acids (SCFAs), which are produced by intestinal flora and transferred by G protein-coupled receptors (GPCRs), resulting in impaired gastrointestinal function, disrupted metabolic processes, increased blood pressure (BP), and ultimately, MH. It is not clear whether Dendrobium officinale polysaccharide (DOPS) can mediate its effects by triggering the SCFAs-GPCR43/41 pathway. In this study, DOPS, with a content of 54.45 ± 4.23% and composition of mannose, glucose, and galacturonic acid at mass percentages of 61.28, 31.87, and 2.53%, was isolated from Dendrobium officinale. It was observed that DOPS, given to rats by intragastric administration after dissolution, could lower the BP and improve the abnormal lipid metabolic processes in ACHSFD-induced MH rats. Moreover, DOPS was found to increase the production, transportation, and utilization of SCFAs, while improving the intestinal flora and strengthening the intestinal barrier, as well as increasing the intestinal levels of SCFAs and the expression of GPCR43/41. Furthermore, DOPS improved vascular endothelial function by increasing the expression of GPCR41 and endothelial nitric oxide synthase in the aorta and the nitric oxide level in the serum. However, these effects were all reversed by antibiotic use. These findings indicate that DOPS is the active component of Dendrobium officinale, and it can reverse MH in rats by activating the intestinal SCFAs-GPCR43/41 pathway.